A Study on Clinico-Epidemiological Profile of Poisoning in Children in a Rural Tertiary Care Hospital - Sil, Archan; Ghosh, Tarak Nath; Bhattacharya, Sudipta; Konar, Mithun Chandra; Soren, Baisakhi; Nayek, Kaustav (Journal of Nepal Paediatric Society, 2016)
Introduction: Poisoning is an important cause of morbidity and mortality in paediatric age group. Objective of this study was to determine the pattern of poisoning in paediatric age group in respect to epidemiological characteristics, aetiology, clinical features and mortality in a major part of South Bengal. Material and Methods: This was a retrospective, observational study conducted in the paediatric medicine ward and paediatric intensive care unit (PICU) of Burdwan Medical College from January, 2015 to December, 2015.All children in the age group of less than or equal to 12 years who visited the paediatric emergency with history of exposure to toxic substances were included in the study. Poisoning due to insect or animal bite was excluded from the study. Data was obtained from hospital records and the admission register of paediatric emergency, entered in the Microsoft excel sheet and analysed by using statistical software SPSS version 17. Results: During the study period, 393 patients with poisoning were reported, which was 1.9% of all pediatric admissions. Majority were in the 1-3 year age group (59.6%). Volatile hydrocarbons accounted for the highest proportion of poisonings (153 cases, 38.9%).. GI system involvement (36.5 %) was most common. The total mortality of poisoning patients was 8. Conclusion: Number of children, presenting with poisoning was higher in our study in comparison to other studies. Volatile hydrocarbons were common source of poisoning in our study. More epidemiological studies are required to identify socio-demographic risk factors of poisoning. J Nepal Paediatr Soc 2016;36(2):105-109.